THE INFLUENCE OF GUIDED INQUIRY LEARNING MODEL USING PhET MEDIA ON THE STUDENTS SCIENCE PROCESS SKILLS OF LIGHT WAVE MATERIALS - Fernando, Richo; Megalina, Yeni ((IPER) Indonesian Physics Education Research, 2020)
This study aims to look at the science process skills of students using guided inquiry learning models assisted by the PhET media on the science process skills (SPS) of light subject matter, students in class XI, second semester, of SMA Negeri 9 Medan Academic Years 2018/2019. The population is all students of class XI semester II. With the cluster random sampling technique, the class XI IPA 1 was selected as the experimental class and XI IPA 2 as the control class. Before the study was conducted, the average pretest value of the experimental class was 38.43 and the control class was 38.31. In testing the normality and homogeneity of the two classes, it is obtained that the data of both classes are normally distributed and homogeneous. Furthermore, in the experimental class guided inquiry learning was carried out using PhET media and conventional learning was carried out in other classes. After learning is given then in the two classes conducted posttest with the average results of the experimental class 83.33 and the control class 70.60. From the results of hypothesis testing, there was an increase in students' SPS due to the influence of the PhET guided inquiry learning model on student™s SPS the of light wave principal.Keywords: Learning Models, guided Inquiry, PhET media, Science Process Skills (SPS)